Connecticut Green Bank 2018 - Elias, Jaan (SAGE Business cases., 2019)
From 2017 to 2018, the Connecticut Green Bank ("CGB") experienced a dramatic change in fortunes. In July of 2017, the Harvard Kennedy School of Government gave the bank its prestigious Ash prize in policy innovation. Less than a year later, the Connecticut legislature "raided" the bank's revenue streams, throwing its existence into doubt. While CGB managed to claw back enough money to survive, the quasi-governmental agency recognized that it needed fresh innovations to fulfil its mission.